A duke worth fighting for - Britton, Christina (Romance fiction writer) (Forever, 2021)
"Daniel Hayle, Duke of Carlisle, returned from Waterloo a hero, dreads the coming London season as he never did the battlefield, where his lack of social skills is certain to make it difficult to find a wife. What he needs is someone to help him practice socializing with the ton. Margery Kitteridge is still mourning the loss of her husband. So when she receives a blackmail letter accusing him of desertion, she's desperate to protect his reputation. The answer to her troubles appears in the form of a damaged, reclusive--and much-too-desirable--duke in need of a wife. She proposes an alliance: she'll help him find a bride, in return for the money to pay off the blackmailer. But working so closely together awakens passions they never imagined possible, and reveals secrets that might tear them apart"--